Editorial [Hot Topic: New Insight in Obesity and Insulin Resistance (Guest Editor: Geltrude Mingrone)] - Mingrone, Geltrude (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2006)
The World Health Organisation has declared that obesity is a disease of pandemic significance, which threatens the developing world as well as developed countries. Over recent years rates of overweight and obesity have escalated rapidly to epidemic proportions in many parts of the world, reflecting increasing consumption of energy dense diets high in fats and sugars, compounded by declining levels of physical activity. Using the standard classification, more than 1.1 billion worldwide are estimated to be overweight, of whom around 320 million are obese. The range of normality for BMI has been estimated at between 20-23 kg/m2 across Africa and Asia, but in Europe and North America this range is shifted towards much higher values (25-27 kg/m2), indicating a substantial higher risks to develop obesity and diabetes. In Europe few countries report obesity rates below 10%. Prevalence rates, particularly among women, rise to more than 20% in countries such as the United Kingdom, Germany, Finland and Greece. The burden for the society is made worse by the spreading of the obesity epidemics in childhood in industrially developed as well as in developing countries. Overweight and obesity affects one in 10 children worldwide, but the rate is double in Europe and three times as much across the entire Americas. Furthermore, the emergence of type 2 diabetes in childhood is a serious development. In the USA, for instance, it has been found out that up to 45% of children with newly diagnosed diabetes have type 2 diabetes and most are overweight or obese at diagnosis. Indeed, obesity is closely linked to type 2 diabetes and, in fact, at the present time, it is estimated that 190 million people worldwide have diabetes and that this will increase to 324 million by 2025. This epidemic is taking place in both developed and developing nations. In the U.S. alone, at least 16 million people have type 2 diabetes, with 1 million more diagnosed annually. The strong relationship between obesity and type 2 diabetes have led to the term